2020
DOI: 10.3390/cells9030774
|View full text |Cite
|
Sign up to set email alerts
|

Lamin A and Prelamin A Counteract Migration of Osteosarcoma Cells

Abstract: A type lamins are fundamental components of the nuclear lamina. Changes in lamin A expression correlate with malignant transformation in several cancers. However, the role of lamin A has not been explored in osteosarcoma (OS). Here, we wanted to investigate the role of lamin A in normal osteoblasts (OBs) and OS cells. Thus, we studied the expression of lamin A/C in OS cells compared to OBs and evaluated the effects of lamin A overexpression in OS cell lines. We show that, while lamin A expression increases dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
3
8
0
Order By: Relevance
“…In support of this, our previous work demonstrates that within osteosarcoma specimens Lamin A/C varies greatly and in dependance on cancer cell aggressiveness (Urciuoli et al, 2020). In support of our work, Evangelisti et al (2020) have confirmed that the condition of low Lamin A expression confers to osteosarcoma cells a significant increase in migration potential, while overexpression of Lamin A reduces their migration ability. Here, we deepened Lamin A/C involvement in osteosarcoma cell tumoral behavior, showing that its reintegration in high metastatic 143B cells, expressing basal low levels of Lamin A/C, restores cell adhesion properties as well as tumor features of low aggressive nonmetastatic osteosarcoma cells.…”
Section: Discussionsupporting
confidence: 88%
“…In support of this, our previous work demonstrates that within osteosarcoma specimens Lamin A/C varies greatly and in dependance on cancer cell aggressiveness (Urciuoli et al, 2020). In support of our work, Evangelisti et al (2020) have confirmed that the condition of low Lamin A expression confers to osteosarcoma cells a significant increase in migration potential, while overexpression of Lamin A reduces their migration ability. Here, we deepened Lamin A/C involvement in osteosarcoma cell tumoral behavior, showing that its reintegration in high metastatic 143B cells, expressing basal low levels of Lamin A/C, restores cell adhesion properties as well as tumor features of low aggressive nonmetastatic osteosarcoma cells.…”
Section: Discussionsupporting
confidence: 88%
“…The aberrant expression of Lamin A/C has been reported in a variety of cancer types with ambivalent roles in tumour progression [13]. Its decreased expression in breast, prostate, colon, ovarian, gastric, and endometrial cancer and osteosarcoma correlated with a reduction in overall patient survival and an increase in metastasis and tumour relapse [15,[28][29][30]. In agreement with these works, in previous papers we also found that LMNA expression was related to a less malignant phenotype in human neuroblastoma [23,26].…”
Section: Discussionsupporting
confidence: 86%
“…Previously, we have demonstrated that an impaired nuclear lamina, due to mutations of the gene encoding lamin A/C, i.e., LMNA , is responsible for an unusual nuclear recruitment of Ankrd2 even under basal conditions [ 18 ]. Of note, lamin A/C has been recently correlated with the migration potential of OS cells [ 19 ]. The subcellular localization of Ankd2 in the OS cell lines was next evaluated by immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%